2019
DOI: 10.1088/1361-6463/ab4856
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-controlled magnetic tunnel junctions with synthetic ferromagnet free layer sandwiched by asymmetric double MgO barriers

Abstract: Memory and computing applications utilizing voltage-controlled magnetic random-access memory (MRAM) require perpendicular magnetic tunnel junctions (pMTJs) capable of high thermal stability and large write efficiency at advanced technology nodes. We first discuss the scaling requirements for voltage-controlled MRAM to replace various existing memory applications at an advanced CMOS technology node, including cell size, thermal stability, interfacial perpendicular magnetic anisotropy (PMA), and voltage-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 111 publications
1
4
0
Order By: Relevance
“…Noting that the MAE of MgO/CoFe/W/CoFe/MgO structure originates from the CoFe/W/CoFe structure and the CoFe/MgO interface, we add up the MAEs of these two parts to get the MAE of the MgO/CoFe/W/CoFe/MgO structure [10,11]. In figure 2 W structures agree well with experimental results [31,32]. Moreover, for the structure with W thickness of 7 MLs, a strong FMC as well as a strong PMA can be obtained simultaneously, which is promising for high-density STT-MRAM applications with strong thermal stability.…”
Section: Discussion and Resultssupporting
confidence: 73%
“…Noting that the MAE of MgO/CoFe/W/CoFe/MgO structure originates from the CoFe/W/CoFe structure and the CoFe/MgO interface, we add up the MAEs of these two parts to get the MAE of the MgO/CoFe/W/CoFe/MgO structure [10,11]. In figure 2 W structures agree well with experimental results [31,32]. Moreover, for the structure with W thickness of 7 MLs, a strong FMC as well as a strong PMA can be obtained simultaneously, which is promising for high-density STT-MRAM applications with strong thermal stability.…”
Section: Discussion and Resultssupporting
confidence: 73%
“…The self-powered nature of the optical tag makes it ideal for implantable devices, or for working with other sensors that can also be operated without significant external power. An example is the spin-torque microwave detector (STMD) based on magnetic tunnel junctions 17 , 18 , 20 , 30 , 34 – 36 , which can operate as an RF detector without the need for external power or external magnetic fields 18 , 19 . Hence, as a proof of concept demonstration of the potential of self-powered sensor tags, we combined the opto-tag with an MTJ-based STMD to produce an RF-to-optical transducer.…”
Section: Resultsmentioning
confidence: 99%
“…2 a. The bottom CoFeB layer was the free layer, featuring an interfacial perpendicular magnetic anisotropy (PMA) originating from the 3d-2p hybridization of Fe and O orbitals at the CoFeB/MgO interface 34 , 36 . The top CoFeB layer was the in-plane reference layer of the MTJ.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, K u t as high as 0.4 mJ m −2 has been reported for a MgO/CF-B/Mo/CFB/MgO structure [22]. Cheng et al [22] have also demonstrated that the MgO/CFB/Mo/CFB/MgO structure sustains a large PMA even after the annealing at 500 • C. However, there are only a few studies on the VCMA effect in these MgO/CFB/X/CFB/MgO structures [23,24] because it is difficult to reduce the total thickness of CFB/X/CFB for quantitatively evaluating ξ. Therefore, in this study, we investigate in detail the PMA in the MgO/CFB/Mo/CFB/MgO structure as a function of CFB and Mo thicknesses in order to achieve a large PMA while reducing the CFB/X/CFB total thickness.…”
Section: Introductionmentioning
confidence: 97%